1999
DOI: 10.1159/000029385
|View full text |Cite
|
Sign up to set email alerts
|

Static Lung Volumes: Reference Values from a Latin Population of Spanish Descent

Abstract: Background and Objectives: The aim of this study was to develop a set of prediction equations and 90% confidence intervals for static lung volumes using the multibreath helium equilibration method from a sample of asymptomatic Caucasian subjects of Spanish descent. Moreover, these equations were compared with those of previous studies. Methods: Measurements of static lung volumes using techniques recommended by the American Thoracic Society and the European Community for Steel and Coal were carried out on a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Differences between observed and predicted values of RV and TLC from previously reported series 1,5,8,9 and the present prediction equations are shown in Table 4. Age‐related differences between former and present reference equations are shown in supporting Tables S1 and S2.…”
Section: Resultsmentioning
confidence: 52%
“…Differences between observed and predicted values of RV and TLC from previously reported series 1,5,8,9 and the present prediction equations are shown in Table 4. Age‐related differences between former and present reference equations are shown in supporting Tables S1 and S2.…”
Section: Resultsmentioning
confidence: 52%
“…Comparisons with the reference equations for TLC, RV and FRC provided by ERS [6], Crapo et al [9], Cordero et al [17] and Garcia-Rio et al [18] are shown in figures 1 and 2 for males and females, respectively. Comparison with the reference equations for TL CO provided by Crapo et al [19], Knudson et al [20], Thompson et al [21] and Aguilaniu et al [22] is shown in figure 3 for males and females separately.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, our study is the largest all-age reference equation-deriving study for TL CO and one of the largest for static lung volumes [17,18]. The following basic criteria, required to obtain the reference values of static lung volumes and diffusion capacity, were fulfilled in our study: (1) a sufficient number of subjects for each sex with an equal representation of each age group; (2) strict inclusion criteria: healthy nonsmoking individuals from the mixed urban and rural populations; (3) standardization of measurements and quality control procedures according to the latest ATS/ERS recommendations, and (4) accurate statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Had we used standard human equations to estimate the Kebara 2 TLC value, we would have obtained values of 6.18 l, 6.20 l and 6.36 l using the formulae from Quanjer et al 48 , Cordero et al 49 and Neder et al 50 , respectively. Therefore, both Kebara 2 and Tabun 1 present much larger values of TLC using our equations than when using human standard equations.…”
Section: Discussionmentioning
confidence: 99%